Prescription Patterns for Pulmonary Vasodilators in the Treatment of Pulmonary Hypertension Associated With Chronic Lung Diseases: Insights From a Clinician Survey - Thomas, Christopher A.; Lee, Justin; Bernardo, Roberto J.; Anderson, Ryan J.; Glinskii, Vladimir; Sung, Yon K.; Kudelko, Kristina; Hedlin, Haley; Sweatt, Andrew; Kawut, Steven M.; Raj, Rishi; Zamanian, Roham T.; et al. (Frontiers in Medicine, 2021)
Background: Pulmonary hypertension is a complication of chronic lung diseases (PH-CLD) associated with significant morbidity and mortality. Management guidelines for PH-CLD emphasize the treatment of the underlying lung disease, but the role of PH-targeted therapy remains controversial. We hypothesized that treatment approaches for PH-CLD would be variable across physicians depending on the type of CLD and the severity of PH. Methods and Results: Between May and July 2020, we conducted an online survey of PH experts asking for their preferred treatment approach in seven hypothetical cases of PH-CLD of varying severity. We assessed agreement amongst clinicians for initial therapy choice using Fleiss’ kappa calculations. Over 90% of respondents agreed that they would treat cases of severe PH in the context of mild lung disease with some form of PH-targeted therapy. For cases of severe PH in the context of severe lung disease, over 70% of respondents agreed to use PH-targeted therapy. For mild PH and mild lung disease cases, less than 50% of respondents chose to start PH-specific therapy. There was overall poor agreement between respondents in the choice to use mono-, double or triple combination therapy with PH-specific agents in all cases. Conclusion: Although management guidelines discourage the routine use of PH-targeted therapies to treat PH-CLD patients, most physicians choose to treat patients with some form of PH-targeted therapy. The choice of therapy and treatment approach are variable and appear to be influenced by the severity of the PH and the underlying lung disease.